GAMBARAN KEHIDUPAN YAKUZA DI MASYARAKAT JEPANG MODERN DALAM FILM OUTRAGE KARYA KITANO TAKESHI - ISLAMIYAH, LUTFIA DWI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Literary work is the description of a certain real event occurred in the community. One from of literary work is movie. This research uses a movie titled with Outrage which describes about yakuza life. Yakuza is a community group in Japan. The problem discussed in this research is how is the description of yakuza life in Japan community in the Outrage movie directed by Takeshi Kitano. The author uses Ian Watt’s literature sociology theory as the approach of research to recognize literature as the mirror for the community in describing the life of yakuza in Japan community and to see how far Outrage movie is in describing yakuza life. Result of research proves that Outrage movie is indeed describing the actual life of yakuza by showing the organization of yakuza, the traditions attended in yakuza, the businesses run by yakuza, the relationship between yakuza groups, and the relationship between police and yakuza. Further research shall use other approaches to understand this movie, such as historical and cultural approaches in order to enrich the appreciation in the literature work. Keywords: movie, literature sociology, yakuza, modern Japan community